Ataturk lessons in leadership from the greatest general of the Ottoman Empire - Bay, Austin (World generals series, 2011)
Mustafa Kemal Atatürk was a Muslim visionary, revolutionary statesman, and founder of the Republic of Turkey. The West knows him best as the leading Ottoman officer in World War I's Battle of Gallipoli-a defeat for the Allies, and the Ottoman empire's greatest victory. Gaining fame as an exemplary military officer, he went on to lead his people in the Turkish War of Independence, abolishing the Ottoman Sultanate, emancipating women, and adopting western dress. Deeply influenced by the Enlightenment, Atatürk sought to transform the empire into a modern and secular nation-state, and during his presidency, embarked upon a program of impressive political, economic, and cultural reforms. Militarily and politically he excelled at all levels of conflict, from the tactical, through the operational, to the strategic, and into the rarified realm of grand strategy. His ability to integrate the immediate with the ultimate serves as an important lesson for leaders engaged in the twenty-first century's great military struggles. He became the only leader in history to successfully turn a Muslim nation into a Western parliamentary democracy and secular state, leaving behind a legacy of modernization and military and political leadership.